Baseline isotopic variability in plants and animals and implications for the reconstruction of human diet in 1 st century AD Pompeii - Silvia Soncin; Valeria Amoretti; Chiara Comegna; Chiara Assunta Corbino; Noemi Mantile; Simona Altieri; Maria Rosa Di Cicco; Valentina Giacometti; Jan Bakker; Marina Caso; Angela Trentacoste; Steven Ellis; et al. (Scientific Reports)
Abstract While Pompeii has long captured the imagination with its history and tragic end, recent efforts have shifted towards unveiling everyday lifeways. Our study seeks to explore agricultural and husbandry practices in Pompeii, aiming to explore isotopic variability of different food categories available to the Romans within this unique “snapshot” scenario. To do so, we deploy stable carbon and nitrogen isotope analysis of plants and animals. Our findings suggest a diversity of practices, with isotopic variation in C3 cereals and legumes pointing to the use of a greater variety of cultivation techniques compared to arboreal crops. We highlight distinct management regimes utilised for different animal species and we uncover a spectrum of aquatic environments, indicative of diversity of fishing practices. These findings provide direct support of archaeological evidence and textual interpretations of Roman food systems in Pompeii. However, our dataset also reveals the limitations of bulk isotope approaches in detecting this dietary diversity when we use it to interpret the local human diet through mixing models. Together, our results show that a broad and well-contextualised isotopic baseline can help us understanding ancient food systems, while also revealing the challenges of disentangling dietary complexity using bulk stable isotope data alone.